Dynamic Changes in Breast Cancer Receptor Status: A Case Report Highlighting the Importance of Repeat Biopsies in Guiding Treatment Strategies - Navkirat Kahlon MD, MPH; Sujatha Baddam MD; Nahush Bansal MD; Zaheer Qureshi MD; Jhansi Maradana MD (Journal of Investigative Medicine High Impact Case Reports)
Breast cancer receptor status plays a critical role in treatment selection, yet receptor evolution throughout disease progression remains a significant challenge. This case describes a 58-year-old female initially diagnosed with estrogen receptor (ER)-positive (95%), progesterone receptor (PR)-negative (<5%), human epidermal growth factor receptor 2 (HER2)-negative (immunohistochemistry [IHC] 0, fluorescence in situ hybridization-negative) invasive ductal carcinoma. Over 6 years, her tumor transitioned to triple-negative breast cancer at recurrence, then reacquired ER expression (80%) in metastatic mediastinal lymph nodes. HER2 status evolved from IHC 0 → HER2-low (IHC 1+ → IHC 2+), directly influencing therapy selection. These receptor changes led to major systemic treatment modifications, including endocrine therapy, immunotherapy, CDK4/6 inhibitors, and antibody–drug conjugates. Given the extended response duration and improved tolerability of targeted therapies, accurate receptor assessment is essential to ensure that patients receive the most effective treatment. Literature reports receptor discordance rates of ER loss (19%), PR loss (34%), and HER2 fluctuations (15%), reinforcing the necessity of biopsy-driven treatment adaptation. While serial biopsies remain invasive, they provide essential molecular insights that optimize systemic therapy choices, allowing patients to remain on the most appropriate, well-tolerated regimen for as long as possible. This case highlights the clinical significance of receptor evolution and advocates for biopsy-guided precision oncology in metastatic breast cancer management. Ensuring accurate receptor reassessment through periodic molecular profiling can maximize therapeutic efficacy, improving response rates, treatment tolerability, and overall patient outcomes.